Genetic parameter estimatives in CMS 35 maize population at Sergipe, Brazil - de Carvalho, Hélio Wilson Lemos; Leal, Maria de Lourdes da Silva; dos Santos, Manoel Xavier (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:ff3; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; h1 mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:1; font-size:24.5pt; font-family:"Times New Roman"; color:black; mso-font-kerning:0pt; mso-ansi-language:PT-BR; font-weight:normal; text-decoration:underline; text-underline:single; h2 mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:2; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:PT-BR; p.MsoBodyText, li.MsoBodyText, div.MsoBodyText margin-top:11.25pt; margin-right:0cm; margin-bottom:0cm; margin-left:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; background:white; font-size:12.0pt; mso-bidi-font-size:11.5pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; color:#333333; mso-ansi-language:PT-BR; span.ff11 mso-style-name:ff11; mso-ascii-font-family:Arial; mso-hansi-font-family:Arial; mso-bidi-font-family:Arial; font-weight:normal; font-style:normal; p.plff1, li.plff1, div.plff1 mso-style-name:"pl ff1"; margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS"; span.ff31 mso-style-name:ff31; mso-ascii-font-family:ff3; mso-hansi-font-family:ff3; font-weight:bold; font-style:normal; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to estimate genetic parameters of CMS 35 population submitted to three selection cycles among and within half-sib progenies in Sergipe State, Brazil, in the 1998/2000 period. In each cycle, 196 half-sib progenies were evaluated in a 14x14 simple lattice in two local sites. The recombinations of the selected progenies were made within the same agricultural year, so that one cycle/year/was obtained. Genetic variability was reduced from the cycle I to the cycle II, and it was increased from cycle II to cycle III. The estimated parameters values associated with mean values for production and with the estimated gain for the selection show the genetic potential of CMS 35 population for increasing production and for good adaptability in the Brazilian Northeast region.